2019
DOI: 10.1007/s40615-019-00635-3
|View full text |Cite
|
Sign up to set email alerts
|

Family First: Asian Americans’ Attitudes and Behaviors Toward Deceased Organ Donation

Abstract: Asian Americans have substantial transplantation needs but the lowest rates of organ donation in the United States. As the shortage of transplantable organs persists, the rate of deceased donation by Asian Americans has not kept pace with that of the general population. This report is a qualitative study of organ donation-related attitudes and beliefs of three Asian ethnic groups located in the greater Philadelphia metropolitan area: Chinese, Filipino, and Vietnamese Americans. Guided by a Community Advisory B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…Demographic factors such as age, gender, education level, occupation and nationality are also associated with being a donor ( 11 13 ). Previous studies have shown that family played an essential role in organ donation ( 14 , 15 ). Researchers collected 1886 questionnaires on organ donation from 11 cities in China, they found that 69.9% of participants considered family consent necessary and 77.1% thought that the view of their family had a great, even decisive, influence on them to decide to become donors ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Demographic factors such as age, gender, education level, occupation and nationality are also associated with being a donor ( 11 13 ). Previous studies have shown that family played an essential role in organ donation ( 14 , 15 ). Researchers collected 1886 questionnaires on organ donation from 11 cities in China, they found that 69.9% of participants considered family consent necessary and 77.1% thought that the view of their family had a great, even decisive, influence on them to decide to become donors ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the fact of perceiving donation as an act of love for others, of solidarity or as an act that saves lives contributes to a favorable decision, but it is not the determining factor in the choice to be a donor or consent to harvesting a relative's organs. The individual may have positive perceptions, but this does not mean that there is a real desire to be a donor (9)(10)24) . In this direction, a Spanish study identified that 1.855 (20%) medical students interviewed were undecided or would deny the donation, a high number considering the area of training (17) .…”
Section: Discussionmentioning
confidence: 99%
“…In general, these taboos are related to beliefs such as the existence of an organ trade market, the practice of euthanasia by health professionals, and the disfigurement of the body after donation. These perceptions are very common and contribute to attitudes against organ donation (7,10,18,24) . This is corroborated by a Mexican study carried out with 331 medical and nursing students, in which it was possible to identify these beliefs, along with fear of pain during the surgical procedure or negligence of professionals (1) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is largely attributed to there being few heart donors in Taiwan, particularly infants and young children. Several major barriers to organ donation have been noted in Asian populations (26)(27)(28). East Asians traditionally desire an intact body at death to comply with the concept of filial piety within Confucianism (26).…”
Section: Discussionmentioning
confidence: 99%